An Empirical Investigation of the Chinese IPO Market - Lin, Shiqiang (2006)
In this paper, I study the underpricing of the 1,072 A-share IPOs and 46 B-share IPOs issued between the periods of 1993 to 2005 in the Chinese market. The average underpricing for A-share is 124.5%, while the average underpricing for B-share IPOs is only 17.8%. I test a number of hypotheses that may help to explain the high degree of underpricing of A-share IPOs in China. The underpricing of IPOs is related to the size of the IPO, the P/E ratio, the proportion of tradable share and the industry characteristics, and it is also affected by the first trading day turnover. I test the short term aftermarket performance and find the new issues tend to decline, this leads to the conclusion that underpricing is also partially due to the market overreaction in the first trading day. The high first day turnover rates of A-share IPOs also imply that domestic investors are more interested in the short-term investment and the market is highly speculative.